2008
DOI: 10.1152/ajpgi.00536.2007
|View full text |Cite|
|
Sign up to set email alerts
|

Progesterone stimulates the proliferation of female and male cholangiocytes via autocrine/paracrine mechanisms

Abstract: During cholestatic liver diseases, cholangiocytes express neuroendocrine phenotypes and respond to a number of hormones and neuropeptides by paracrine and autocrine mechanisms. We examined whether the neuroendocrine hormone progesterone is produced by and targeted to cholangiocytes, thereby regulating biliary proliferation during cholestasis. Nuclear (PR-A and PR-B) and membrane (PRGMC1, PRGMC2, and mPRα) progesterone receptor expression was evaluated in liver sections and cholangiocytes from normal and bile d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 77 publications
4
58
0
1
Order By: Relevance
“…The nature of these cells, that is, whether they are fibroblasts, endothelial cells, transformed hepatocytes, or biliary ductules, is a subject of debate [6] . One of the functional characteristics of proliferating cholangiocytes is that they acquire a neuroendocrine phenotype, especially in "atypical" ductular reaction [9,32,34,35] . Proliferating cholangiocytes, from "atypical" proliferation, show phenotypical features of neuroendocrine cells like chromogranin A, S-100 protein glycolipid A2-B4, and a neural cell adhesion molecule [9] .…”
Section: Cholangiocyte Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of these cells, that is, whether they are fibroblasts, endothelial cells, transformed hepatocytes, or biliary ductules, is a subject of debate [6] . One of the functional characteristics of proliferating cholangiocytes is that they acquire a neuroendocrine phenotype, especially in "atypical" ductular reaction [9,32,34,35] . Proliferating cholangiocytes, from "atypical" proliferation, show phenotypical features of neuroendocrine cells like chromogranin A, S-100 protein glycolipid A2-B4, and a neural cell adhesion molecule [9] .…”
Section: Cholangiocyte Proliferationmentioning
confidence: 99%
“…Proliferating cholangiocytes, from "atypical" proliferation, show phenotypical features of neuroendocrine cells like chromogranin A, S-100 protein glycolipid A2-B4, and a neural cell adhesion molecule [9] . During cholestatic liver diseases, the cholangiocytes express neuroendocrine phenotypes and respond to a number of hormones and neuropeptides [34] . For example, these proliferating cholangiocytes have increased expression and secretion of serotonin, endogenous opioid peptides and neurothrophins (and their corresponding receptors) [25] .…”
Section: Cholangiocyte Proliferationmentioning
confidence: 99%
“…Cholangiocyte hyperplasia is regulated by a number of factors including gastrointestinal hormones (24,46), cyclic adenosine 3Ј,5Ј-monophosphate (cAMP) (20), angiogenic growth factors [e.g., vascular endothelial growth factor (VEGF)] (17,21) and sex hormones such as estrogens (8), prolactin (58), and progesterone (25). The cAMP/ERK1/2/Elk-1 signaling has been shown to play a key role in the regulation of cholangiocyte proliferation (18,20,24,27,37).…”
Section: )] (41)mentioning
confidence: 99%
“…Whether the FSH receptor is also linked to G␣ i has not yet been completely defined. In fact, the treatment of Sertoli cells with pertussis toxin (PTX, a G␣ i inhibitor) (29), an agent capable of removing the tonic inhibitory effects of G␣ i , increases FSH-induced aromatase activity, suggesting that the inhibitory activity of G␣ i may negatively modulate the PKA pathway of signal transduction (30).Studies have demonstrated the role of sex hormones in the regulation of the growth of the biliary epithelium (8,9,25,58). For example, in concert with growth factors, estrogens sustain cholangiocyte proliferation and reduce cholangiocyte apopto-…”
mentioning
confidence: 99%
“…Відомо, що гормони репродуктивної системи -естрогени, пролактин, фолітропін, прогесте-рон -чинять суттєвий вплив на холангіоцити, утворення та секрецію жовчі [1][2][3]. Ймовірна участь тестостерону у цих процесах підтвер-джується наявністю рецепторів андрогенів у гепатоцитах і холангіоцитах [4][5][6].…”
Section: вступunclassified